USO DE ÓLEO ESSENCIAL DA LIPPIA ORIGANOIDES NO DESEMPENHO PRODUTIVO DO PACU (PIARACTUS MESOPOTAMICUS) - XAVIER, Vitória Maria Gregório; MENDEZ, Victor Hugo Benassi; ACUNHA, Rubia Mara Gomes; 2ALMEIDA, Rômullo Guilherme dos Santos; AMARAL, Cristiane Meldau de Campo (ANAIS DO ENIC, 2024)
-